Sistem Pemantauan Kualitas Udara Berbasis IoT di Peternakan Yakin Telur - Hendri; Pribadi, Octara; Hendrik, Jackri (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Air quality in poultry farms plays a crucial role in animal productivity, as poor air quality can increase the risk of disease in chickens, cause stress, and ultimately reduce productivity and egg quality, leading to economic losses for farmers. Laying hens require stable and adequate temperature conditions during their growth period to ensure optimal development. The optimal temperature for laying hens during the brooding period (up to 14 days old) ranges between 30-32°C. A common issue faced by livestock farmers is the lack of adequate facilities to manage stress in livestock, which often hinders their ability to stabilize the air temperature in the chicken coop. Farmers often rely on manual methods to estimate and adjust the temperature inside the coop by feeling the heat, which is neither accurate nor efficient. This research aims to design an IoT-based air quality monitoring system at Yakin Telur Farm. The system is designed to monitor temperature, humidity, and ammonia gas levels in the chicken coop in real-time.